A Cryptographic Confusion Primitive Based on Lotka-Volterra Chaotic System and Its Practical Applications in Image Encryption - Muhammad, Zahir Muhammad Ziad; Ozkaynak, Fatih (Ieee, 2020)
New attacks on existing algorithms have revealed various weaknesses. To overcome these weaknesses, researchers are searching for new ones. In this study, a new image encryption algorithm has been proposed to realize this aim. The most obvious component of the proposed image encryption algorithm is the cryptographic substitution box structure used to provide the confusion requirement. The original aspect of the substitution box structure according to similar studies in the literature is that the design was realized by using Lotka-Volterra chaotic system. The analysis results showed that both the substitution box structure and the image encryption algorithm provide the necessary criteria for data security.
15th International Conference on Advanced Trends in Radioelectronics, Telecommunications and Computer Engineering (TCSET) -- FEB 25-29, 2020 -- Lviv, UKRAINE
Keywords: chaos; cryptography; substitution box; image encryption